Prophylactic intramedullary nailing of the proximal femur in a case of McCune Albright syndrome – A case report & review of literature - Mrinal Mahadev Kambli; Shaswat Mishra; Sagar Bansal; Sachin Khemkar; Sanjeev Ghildiyal; Manish Jain (Journal of Orthopaedic Reports, 2023)
Introduction: Premature puberty, café-au-lait pigmentation, polyostotic fibrous dysplasia, and/or varied endocrine disorders make up the unusual condition known as McCune Albright Syndrome. If not treated promptly, polyostotic fibrous dysplasia of the long bones results in severe limb abnormalities ultimately leading to pathological fractures. This is a case report describing a case of McCune Albright Syndrome where early diagnosis and prophylactic fixation prevented deformity and pathological fractures. Case report: An adolescent 15-year-old male was brought by relatives with left hip and thigh discomfort that has persisted for three years. Patient's history and full body examination revealed early puberty and café-au-lait spots. After haematological and radiological tests, such as plain radiographs, MRIs, and bone scans to look for further sites of involvement, the left femur was prophylactically fixed with a long proximal femoral nail, and local curettage of the lesion was done. At the 3-year follow-up, the patient had satisfactory pain alleviation and no evidence of a recurrence. Conclusion: In cases of McCune Albright Syndrome, prophylactic fixation of lesions of the proximal femur results in great pain alleviation, deformity prevention, and lowers the risk of pathological fractures, as seen in this case.